Analysis of the Implementation of Marketing Strategy Using a CRM Approach to Increase Probiotic Sales Revenue at PT. Agrikencana Perkasa - Mardriatama, Jati Shobri; Kussudyarsana (Jurnal Economic Resource, 2025)
In the increasingly competitive agricultural biotechnology sector, sales instability remains a challenge, particularly in the probiotic industry. PT. Agrikencana Perkasa has experienced fluctuating sales performance, urging the need for an effective and sustainable marketing strategy. This study aims to analyze the implementation of marketing strategies using a Customer Relationship Management (CRM) approach to increase probiotic sales revenue at PT. Agrikencana Perkasa. A qualitative research method was employed, with data collected from interviews, observations, and documentation. The research involved key informants including company managers and decision-makers, selected through purposive sampling. The study was conducted at PT. Agrikencana Perkasa, located in Klaten Regency, Central Java, from February to April 2025. Findings revealed that the company applies CRM through customer education and Boss-to-Boss business-to-business (B2B) marketing. CRM strategies were implemented via customer empowerment, personalized product explanation, loyalty programs, and digital content, while the B2B approach was applied through direct interactions between top-level executives. These strategies contributed to improved customer trust, loyalty, and repeated purchases. Furthermore, the integration of CRM and tailored digital marketing platforms, although still limited, supports the company’s sales growth. The implications of this study highlight the importance of personalized engagement and executive-level partnerships in bio-agriculture marketing practices, serving as a reference for similar businesses facing unstable markets.